Towards greener disposal of waste cathode ray tubes via ultrasonically enhanced lead leaching - Saterlay, A; Wilkins, S; Compton, R (2001)
The disposal of waste cathode ray tubes (CRT) from old televisions and discarded computer monitors is rapidly becoming an issue of growing environmental concern due to the leaching of lead and other toxins by groundwater from landfill sites. Imminent legislation in both the EU and the USA is likely to demand much stricter control on the disposal of such hazardous electronic equipment, with a drive towards lead removal prior to landfill and/or recycling. This paper describes the use of power ultrasound to facilitate the removal of lead from the heavily-leaded CRT glass via an accelerated leaching protocol, with the aim of producing a lead-free product for greener disposal or more ideally for glass recycling purposes. The paper also describes the use of cathodic stripping voltammetry at a boron-doped diamond sensor, as a quick, easy and cost-effective technique for monitoring the rate of lead released from the CRT glass into a mildly acidic leachate.